Effect of yoghurt or yoghurt serum on microbial quality of cig kofte - Dogan, Mahmut; Cankurt, Hasan; Toker, Omer Said; Yetim, Hasan; Sagdic, Osman (SPRINGER INDIA, 2014)
Cig kofte, raw meatball is a traditionally produced meat product in Turkey and some other Middle East countries. It is prepared from mixtures of finely minced raw beef, bulgur, onions, various spices and tap water. Cig kofte is an uncooked product and popularly consumed with lettuce and lemon juice. In this study, yoghurt or yoghurt serum (YS) were added to the mixtures of cig kofte instead of tap water to reduce microbial risks of the raw meatball. Additionally, the effects of yoghurt and YS on some physicochemical characteristics of cig kofte were investigated. Cig kofte is generally consumed within a few hours after the preparation because of its raw nature. Also, it is generally sold under unhygienic conditions in restaurants and restaurant-like places. For this purpose, reducing of the microbial load of cig kofte is important. In the results, Escherichia coli and Listeria monocytogenes were not detected in any samples. While lactic acid bacteria count increased by addition of yoghurt and YS, the number of other microorganisms except for total aerobic mesophilic bacteria (TAMB) were decreased. The a(w) values and% moisture contents of the samples were varied between 0.88-0.94 and 46.25-49.72, respectively. The pH values of the samples were slightly changed during the storage of 24 h while no changes detected in the control samples during the storage. In conclusion, it can be suggested that using the yoghurt or YS instead of tap water in the preparation of cig kofte might ensure the microbial safety, increase the nutritional value and its flavour or aroma.
Keywords: Cig kofte; Yoghurt; Yoghurt serum; Microbiological load; DIFFERENT STORAGE TEMPERATURES; MICROBIOLOGICAL QUALITY; GAMMA-IRRADIATION; GROWTH; Food Science & Technology